Soldiers as workers - Mansfield, Nick (Historian) (Studies in labour history., 2016)
This book offers the first encounter between labour history and military history, with an analysis of the working lives of nineteenth British rank and file soldiers in the context of a developing working class industrial culture and in its interaction with British society.